Analysis of human remains from a crematory burial ground of Przeworsk culture at Bieżyń (site 1) - Budnik, Alicja (Anthropological Review, 1984)
The paper presents results of morphological analysis of cremated bones of 67 individuals (76 subadults, 28 adults and 13 “indeterminable” ones) buried at a cemetery of Przeworsk Culture dated at stages B1, and B2, of the Roman Period. The state of preservation of human remains was bad, so that sex was ascertained only in 14 cases (8 males, 6 females). Elaboration of the material was carried with use of commonly accepted in physical anthropology and paleodemography methods (Henneberg 1975, 1977, Henneberg et al. 1975, Henneberg and Piontek 1975, Henneberg and Strzałko 1975, Strzałko et al. 1973). Life tables were constructed for stationary population (table 1 and 2) and for stable population (table 3) and Rpor, Ibs values as well as population pyramid were calculated. Comparison of the results obtained by the present author with data given for other burial grounds [Gładykowska-Rzeczycka 1974, Henneberg 1975, Kapica 1974, Malinowski 1969, Mucha 1978, Piontek 1979] allows to conclude that burial ground at Bieżyń is characterized by the higher than average percentage of deceased subadults and other parameters lying close to the lower limit for the Roman Period cemeteries.